Anemia In Children With Chronic Kidney Disease: Literature Review - Purnamawati, IGA Dewi; Safitriani, Indah (Jurnal EduHealth, 2022)
The World Health Organization (WHO) defines anemia as a condition in which the hemoglobin level in the blood decreases to less than 12 g/dL in women and less than 13 g/dL in men. Objective: The Literature Review study provides an overview of children with anemia, the causes, impacts, and management was given to improve anemia in children with Chronic Kidney Disease (CKD). Methods: literature review through database searches: Google Scholar, Proquest, EBSCO, and Science Direct database from 2017 to 2022. Selected studies with anemia criteria, evaluation, and management of anemia in children with CKD. Results: There were six studies in the review which described CKD children as having anemia, anemia caused by multifactor, the impact is an increased risk of hospitalization and death as well as the emergence and development of cardiovascular disease. Conclusion: Anemia that occurs in CKD children gives a picture of low quality of life, high morbidity, and mortality. That comprehensive care is needed between children, parents, nurses, doctors, and nutritionists to reduce the impact of anemia so that quality of life increases